2022
DOI: 10.3390/ijms23063280
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Transcriptomic Analysis Reveals That HSP90AB1 Is Involved in the Immune and Inflammatory Responses to Porcine Deltacoronavirus Infection

Abstract: PDCoV is an emerging enteropathogenic coronavirus that mainly causes acute diarrhea in piglets, seriously affecting pig breeding industries worldwide. To date, the molecular mechanisms of PDCoV-induced immune and inflammatory responses or host responses in LLC-PK cells in vitro are not well understood. HSP90 plays important roles in various viral infections. In this study, HSP90AB1 knockout cells (HSP90AB1KO) were constructed and a comparative transcriptomic analysis between PDCoV-infected HSP90AB1WT and HSP90… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…This result was also confirmed by another NFκB inhibitor SC75741 ( Fig. S5B ) ( Reda et al, 2022 ; Zhao et al, 2022 ). Curiously, when treating cells with rapamycin (RAPA), a mTORC1-specific inhibitor, the activation of NFκB cannot be repressed, which may explain the unidirectional regulatory effect of NFκB on mTORC1 ( Figs.…”
Section: Resultssupporting
confidence: 66%
“…This result was also confirmed by another NFκB inhibitor SC75741 ( Fig. S5B ) ( Reda et al, 2022 ; Zhao et al, 2022 ). Curiously, when treating cells with rapamycin (RAPA), a mTORC1-specific inhibitor, the activation of NFκB cannot be repressed, which may explain the unidirectional regulatory effect of NFκB on mTORC1 ( Figs.…”
Section: Resultssupporting
confidence: 66%
“…Transcriptome analysis was used to quantitatively identify DEGs after PDCoV infection in ST cells. PDCoV infection activates the NF-κB signaling pathway and leads to the expression of inflammatory factors, which may be related to TLRs, but TLR2 is not a critical factor [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HSPA8 interacts with PRRSV GP4 through its PB domain and participates in the attachment and internalization of PRRSV [36]. HSP90AB1, a member of the HSP90 family, is involved in the immune and inflammatory responses to COVID-19 [37], ASFV [38], and PDCoV [39]. It is an attractive antiviral target.…”
Section: Discussionmentioning
confidence: 99%